2017
DOI: 10.1111/jai.13325
|View full text |Cite
|
Sign up to set email alerts
|

Length-weight relationships of two mugilid species from tropical estuarine systems in Alagoas, northeastern coast of Brazil

Abstract: Summary Length‐weight relationships were estimated for two mugilid species from estuarine systems in Alagoas, northeastern Brazil. Fish were sampled monthly using nylon monofilament gillnets with different mesh sizes during two fishery surveys. The first LWR reference for Mugil curvidens and new maximum lengths for both M. rubioculus and M. curvidens are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Recent studies have pointed to the presence of six taxonomically recognized Mugil species in the Coral Coast MPA: Mugil brevirostris , M. curema , M. curvidens , M. incilis , M. liza , M. rubrioculus (da Silva, Teixeira, Batista, & Fabré, 2017, 2018; Torres et al., 2008), although the distribution of M. incilis has been contested (Menezes et al., 2015). Our study used 11 morphological traits to test whether the individuals identified as belonging to these six species are morphologically different.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have pointed to the presence of six taxonomically recognized Mugil species in the Coral Coast MPA: Mugil brevirostris , M. curema , M. curvidens , M. incilis , M. liza , M. rubrioculus (da Silva, Teixeira, Batista, & Fabré, 2017, 2018; Torres et al., 2008), although the distribution of M. incilis has been contested (Menezes et al., 2015). Our study used 11 morphological traits to test whether the individuals identified as belonging to these six species are morphologically different.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on Length-Weight Relationship (LWR) are very limited [45]- [50]. The study of LWRs is considered important to obtain different types of information such as growth rates, age structures, age at first maturity, stock discrimination and studies on population dynamics [50]- [58] to subsidize futures and betters fisheries managements around the world. Other than that, LWRs can also be used to find the relative condition factor, establish-Open Access Library Journal ing performance equations to estimate the number of fish landings and compare the population in space and time [59].…”
Section: Introductionmentioning
confidence: 99%
“…al., 2017;da Silva et al, 2017). In addition, the length-weight relationships can also be used to calculate relative condition factor, setting yield equations for estimating the number of fish landed and in comparing the population in space and time (Le Cren, 1951) and length-length associations are important in comparing growth studies using different length types (Moutopoulos & Stergiou, 2002;Yılmaz et al, 2010;Kashyap et al, 2014;Tsagarakis et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The study of length-weight (LWR) and length-length (LLR) relationships is considered to be important to get different kinds of information of fish in fish biology such as growth rate, age structure, age at first maturity, discrimination of stocks and population dynamic studies (Kohler et al, 1995;Stergiou & Politou, 1995;Morey et al, 2003;Sinovcic et al, 2004;Vaslet et al, 2008;Borah et al, 2017;Ergüden et. al., 2017;da Silva et al, 2017). In addition, the length-weight relationships can also be used to calculate relative condition factor, setting yield equations for estimating the number of fish landed and in comparing the population in space and time (Le Cren, 1951) and length-length associations are important in comparing growth studies using different length types (Moutopoulos & Stergiou, 2002;Yılmaz et al, 2010;Kashyap et al, 2014;Tsagarakis et al, 2015).…”
Section: Introductionmentioning
confidence: 99%